La producción familiar como alternativa de un desarrollo sostenible para la Amazonía: lecciones aprendidas de iniciativas de uso forestal por productores familiares en la Amazonía boliviana, brasilera, ecuatoriana y peruana - Pokorny B.; Godar, Javier; Hoch, L.; Johnson, J.; Koning, J. de; Medina, G.; Steinbrenner, R.; Vos, V.; Weigelt, J. (Center for International Forestry Research, 2010)
Between 2005 and 2009, the EU-financed project ForLive set out to analyse promising local forest management initiatives in the Amazon Basin in four countries: Ecuador, Bolivia, Brazil, and Peru. Researchers aimed to identify locally viable practices that benefit livelihoods and ecological stabilisation of landscapes, as well as to define ways to promote these practices as a basis for sound rural development. This book presents lessons learnt from more than 100 studies by researchersfrom Latin America, from practitioners and from local families themselves. The findings suggest that the focus of current development strategies designed to support smallholders in adopting management and organization, which are usually externally defined systems made from expert-driven policy and research, mayrequire a review of fundamental assumptions and methods. Most of these initiatives widely ignored the immense potential of Amazonian smallholders—settlers, traditional communities and indigenous groups—to contribute to sound rural development with their own ideas and knowledge. Strong evidence was found that the socio-productive systems of Amazonian smallholders could serve as a reference for new methods that support a more equitable and environmentallysustainable development of the region.